Hemophagocytic lymphohistiocytosis secondary to visceral leishmaniasis in an endemic area in the north of Minas Gerais, Brazil - Carvalho,Fernando Henrique Guimarães de (2020)
Abstract INTRODUCTION Visceral leishmaniasis (VL) is an ill-studied disease that is endemic to several regions of Brazil. It is often complicated by hemophagocytic lymphohistiocytosis (HLH), a potentially fatal disorder resulting from excessive non-malignant activation/proliferation of T lymphocytes and macrophages. Considering the overlapping clinical and laboratory characteristics of these diseases, diagnosing HLH is a challenge. Therefore, tracking the association between VL and HLH is necessary in endemic areas. Although HLH can be inapparent and resolve with antileishmanicides, this may not always occur. HLH causes high lethality; therefore, immunosuppressive therapy should be instituted immediately in order to avoid a fatal outcome. METHODS: We described the epidemiological, clinical, laboratory, and therapeutic profile of this association in a region of Brazil endemic for VL. RESULTS We presented 39 patients with this association in a retrospective cohort of 258 children who were admitted from January 2012 to June 2017. Of the 39 patients, 31 were from urban areas (79.5%), and 21 (53%) were males. The mean age and weight were 2.86 (2.08) years and 14.03 (5.96) kg, respectively. The main symptoms were fever (100%), hepatosplenomegaly (100%), pallor of the skin and mucosa (82.5%), edema (38.5%), bleeding (25%), and jaundice (7.5%). Hemophagocytosis was identified in 16/37 (43.24%) patients, and direct examination revealed that 26/37 (70.27%) patients were positive for VL. The patients were treated as recommended by the Ministry of Health. CONCLUSIONS It was observed that HLH is a common complication in endemic areas, and its diagnosis must consider the overlapping of clinical characteristics and pancytopenia.